2006
DOI: 10.1055/s-2006-947362
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Halogen-Metal Exchange Reaction of 3-Substituted 1,2-Dibromo Arenes: The Synthesis of 2-Substituted 5-Bromobenzoic Acids

Abstract: Regioselective halogen-metal exchange reactions using isopropylmagnesium chloride were carried out on 3-substituted 1,2-dibromo arenes. Eleven examples are given.A common strategy in organic synthesis is the functionalization of polyhalogenated arenes. Primarily, iodo-bromo arenes are used in the regioselective functionalization. In recent years, increasing efforts have been made to investigate the regioselective functionalization of diiodo-or dibromo arenes. [2][3][4][5] In 1,4-and 1,3-dibromo arenes, a regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…A series of 3-substituted 1,2-dibromobenzene analogs were prepared to examine the effect of R-group substitution on regioselectivity in the transmetalation. 4 To simplify the analysis, the metal analogs were quenched with carbon dioxide to provide the more stable benzoic acid analogs for product yield via HPLC analysis. NMR analysis was used to determine the regiochemistry of these analogs, which required the use of the older, more traditional 1-D technique:…”
Section: Introductionmentioning
confidence: 99%
“…A series of 3-substituted 1,2-dibromobenzene analogs were prepared to examine the effect of R-group substitution on regioselectivity in the transmetalation. 4 To simplify the analysis, the metal analogs were quenched with carbon dioxide to provide the more stable benzoic acid analogs for product yield via HPLC analysis. NMR analysis was used to determine the regiochemistry of these analogs, which required the use of the older, more traditional 1-D technique:…”
Section: Introductionmentioning
confidence: 99%
“…8 Other pioneering work from the group of Karsten Menzel reported regioselective Metal-bromine exchange reaction of 3-substituted 1,2-dibromoarenes for the synthesis of ortho-bromobenzoic acid derivatives, the authors isolated the products in good yields and concluded that the reactivity and regioselectivity of these substrates per se are affected by the type of substituent at position 3 favoring the metal-bromine exchange reaction to occur exclusively either at position 1 or 2. 23 We envisioned that 1,2,3-triiodoarene derivatives could be regioselective functionalized in a metal-iodine exchange reaction. Having just two regiochemically distinct sites occupied with iodine, metal-iodine exchange/functionalization sequence can give rise to not more than two possible regioisomers, the terminal and the internal diiodobenzyl alcohol products as shown in Scheme 1.…”
Section: Resultsmentioning
confidence: 99%
“…reported regioselective metal–bromine exchange reactions of 3‐substituted‐1,2‐dibromoarenes for the synthesis of ortho ‐bromobenzoic acid derivatives. The products were isolated in good yields and concluded that the reactivity and regioselectivity of these substrates per se are affected by the type of substituent at the C3 position, favoring the metal–bromine exchange reaction exclusively either at the C1 or C2 position 23…”
Section: Resultsmentioning
confidence: 99%